Pengaruh Perhatian Orang Tua Dan Motivasi Belajar Terhadap Prestasi Belajar Pada Mata Pelajaran Pendidikan Kewarganegaraan Di Kelas XI PMIA SMA Negeri 1 Pematang Siantar Tahun Ajaran 2022/2023 - Meydo Rosa Putri Br Girsang; Sepriandison Saragih; Daulat Nathanael Banjarnahor (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aims to find out whether or not the Influence of Parental Attention and Motivation on Student Learning Achievement. This research has been carried out in SMA Negeri 1 Pematang Siantar. Where the class that becomes the population and research sample is XI PMIA as many as 63 people. The data obtained through the Microsoft Excel application. Based on the discussion of research data analysis, the results of hypothesis testing are obtained by calculating the linear regression equation, namely Y over X1 is =79,49 + 0,09X1 , Y over X2 is = 77,59 + 0,10X2 ,Y over X1 and X2 is = 2,65 + 1,93X1 + 2,77X2. The coefficient of influence obtained is the effect of X1 on Y 1.63, the effect of X2 on Y 0.27, the effect of X1 on X2 0.96, the effect of X1 and X2 on Y 5.50. While the coefficient of Y on X1 is 14.62%, the coefficient of Y on X2 is 40.09%, the coefficient of X1 on X2 is 50.68%, the coefficient of Y on X1 and X2 is 3.02%